Assessing motivation to quit smoking in people with mental illness - Siru, R.; Hulse, G.; Tait, Robert (Wiley-Blackwell Publishing Ltd., 2009)
Background People with mental health (MH) disorders smoke at higher rates, are more nicotine-dependent and suffer greater morbidity and mortality from smoking-related illnesses than the general population. Helping these people to quit smoking is a public health priority; however, many MH professionals assume that those with mental illness are not motivated to quit. Objectives To use predetermined criteria to identify, review critically and evaluate empirically all English language, peer-reviewed data on motivation to quit smoking in MH populations. Methods A systematic search was conducted and key data on subject characteristics, measures of motivation and other variables abstracted. ?2 analyses were used to compare motivation between MH and general populations, between in-patients and out-patients and between people with depression and people with psychotic disorders. Results Evidence suggests that people with MH disorders are as motivated to quit smoking as the general population, although those with psychotic disorders may be less motivated than individuals with depression. Although readiness to cease smoking was assessed in 14 studies, only two evaluated motivation to quit smoking in in-patient populations. Conclusions People with MH disorders are motivated to quit smoking, although more research is needed looking at in-patient populations. The commonly held false belief that people with MH disorders are not motivated to cease smoking means that opportunities to encourage smoking cessation among this disenfranchised group are being missed. © 2009 Society for the Study of Addiction.